PERGAULAN DAN PENCEGAHAN KEKERASAN SEKSUAL PADA REMAJA PERSPEKTIF ILMU FIQIH - Sarah Nur’aeni Khoiriyah; Ivana Maulia Rahmah; Mohammad Sobirin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Sexual violence often occurs in society, especially among adolescents. This phenomenon is very worrying because it has an impact on their future. Parents' high activity levels ignore important things that are the vital needs of their children. Sexual violence is an unavoidable phenomenon. Shows that are not guidance, disturbing relationships are other factors. Parents' understanding of providing education about sex can still be said to be minimal, because Sex Education in society is still considered taboo. Teachers as educators in schools can help provide an understanding of Sex Education to students so that students' knowledge needs are met, especially Sex Education according to Islam. (Andriani & Yuningsih, 2023) This article discusses how the principles of social jurisprudence can be implemented as a preventive strategy against sexual violence against adolescents. This study uses a qualitative-descriptive approach with a literature study of sources of fiqh, data on cases of sexual violence, and the concept of Islamic education. The results of the discussion show that internalization of the values of social jurisprudence in education is very relevant to strengthening character and forming students' self-awareness in facing social challenges. This article suggests the need for guidance for adolescents from Islamic Religious Education teachers and parents to bridge the gap between Islamic principles and contemporary trends, emphasizing the importance of Islamic jurisprudence education in adolescence as a basis for living life according to Islamic values. (Muh Yusuf et al., 2023)